La performance en lecture des élèves québécois de 4e année du primaire : comparaison des notes avant et après les fermetures scolaires associées à la pandémie de COVID-19 - Côté, Sylvana; Haeck, Catherine; Collet, Ophélie; Sauve, William; Larose, Simon (Canadian Journal of Education/Revue canadienne de l'éducation, 2024)
Due to COVID-19 prevention measures, schools in Quebec were closed in 2020 and 2021, reducing instructional time compared to previous years. This study compares the reading performance of Grade 4 students on ministerial tests before (June 2019, n = 13,669) and after (June 2021, n = 10,880) school closures while quantifying variations based on students’ individual and socio-economic characteristics. Results reveal a signi-ficant decrease of 8.4 percentage points between 2019 (mean = 77.7%) and 2021 (mean = 69.27%) and an increase of 10.8% in the failure rate (17.1% in 2019 versus 27.9% in 2021). Students in the bottom 10% of the distribution experienced marked declines in performance (-18 percentage points), while students in the top 10% of the distribution did not exhibit any decline. This study contributes to the understanding of the impact of school closures on children’s reading competencies and underscores the critical impor-tance of in-person instruction, particularly for students with learning difficulties.